Composite iron oxide particle powder and method for producing same
By using sodium carbonate and iron oxide compound iron oxide particles powder, the fixation and recycling of carbon dioxide in small and medium -sized facilities are realized in small and medium -sized facilities, and the restrictions of the use of dangerous substance liquids in existing technologies have low energy consumption and high efficiency. Features.
Patent Information
- Application Number
- CN202380047276.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-14
- Filing Date
- 2023-06-02
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to effectively fix and recover carbon dioxide in small and medium-sized facilities, especially due to the use of liquids with hazardous substances, which makes it difficult to apply in small and medium-sized facilities.
The composite iron oxide particles containing sodium carbonate and iron oxide components with a weight of more than 25 % and less than 60 % of the weight of 60 % is used to fix carbon dioxide in the room temperature from room temperature to 100 ° C through fixing reasons, and recovered below 150 ° C.
The carbon dioxide is fixed in the range of room temperature to 100 ° C, and it is recycled below 150 ° C. It has excellent formability and processability. It is suitable for carbon dioxide fixed recycling materials for non -risk substances.
Smart Images

Figure BDA0005188282190000151 
Figure BDA0005188282190000152 
Figure BDA0005188282190000153
Abstract
Description
Technical Field
[0001] The present invention provides a composite iron oxide particle powder for fixing carbon dioxide and a method for producing the same. Background Art
[0002] In 2015, the Paris Agreement was formulated, and in order to fully control the increase in global average temperature within 2°C, the goal is to achieve net zero emissions of greenhouse gases that cause global average temperature increases. Among them, as a government policy, a medium-term goal of reducing greenhouse gas emissions by 26% by 2030 compared to 2013 has been formulated. The main greenhouse gas is carbon dioxide produced by the combustion of fossil fuels. It is reported that the concentration of carbon dioxide in the atmosphere was about 300ppm in the 1950s, and has exceeded 400ppm in recent years. As a trump card to reduce carbon dioxide emissions in the atmosphere, research on the recovery, storage, and recycling of carbon dioxide is underway.
[0003] The major source of carbon dioxide is the exhaust gas emitted from the combustion of fossil fuels in various places. Examples include thermal power plants, boilers in manufacturing plants, and kilns in cement plants that use coal, heavy oil, and natural gas as fuel. In addition, there is also carbon dioxide emitted from blast furnaces in steel plants that use coke to reduce iron oxide, or from transportation vehicles such as cars, ships, and airplanes that use gasoline, heavy oil, and light oil as fuel.
[0004] At present, in large-scale facilities such as thermal power plants, carbon dioxide contained in the exhaust gas is absorbed by contacting with an aqueous amine solution such as alkanolamine. In addition, it is then heated to about 120°C and the absorbed carbon dioxide is recovered. These attempts have been carried out on a large scale and have achieved great results (Patent Documents 1-2). This method uses a liquid absorbent material, so it has the advantage that the absorbent material can be transported by a pump. Therefore, it is easy to scale up. Amine-based carbon dioxide recovery materials are actually used in thermal power plants, steel mills, etc.
[0005] However, since this method uses a liquid of a hazardous substance, it is difficult to use the liquid of a hazardous substance in small and medium-sized facilities such as waste incineration plants that exist in more than 1,800 locations in Japan. As a result, the current situation is that the fixation and recovery of carbon dioxide is almost impossible. At present, the total carbon dioxide emissions in Japan are showing a slight downward trend. Therefore, it is possible to fix and recover carbon dioxide in the above-mentioned small and medium-sized facilities, and the operation is easy. It is expected that the fixation and recovery of solid carbon dioxide without hazardous substances such as amines and at a low price can be achieved.
[0006] Conventionally, as solid carbon dioxide fixation recovery materials, there are known solids loaded with the above-mentioned alkanolamine (Patent Document 3), or barium orthotitanate (Patent Document 4), and lithium ferrite (Patent Document 5).
[0007] Sodium ferrite (Patent Document 6, Non-Patent Documents 1 and 2) is also known as a material that can fix and recover carbon dioxide. Among them, in α-sodium ferrite with a layered rock salt structure (trigonal system), carbon dioxide and sodium undergo a topological chemical reaction. That is, in the reaction with carbon dioxide, α-sodium ferrite becomes Na 1-x A mixed phase of FeO2 and sodium carbonate. Therefore, it is reported that the reaction rate is fast and the carbon dioxide absorption / release repetition performance of the reaction is excellent. On the other hand, it is reported that since sodium in the orthorhombic β-sodium ferrite reacts with carbon dioxide, the crystalline phase of β-sodium ferrite absorbs more carbon dioxide than the crystalline phase of α-sodium ferrite.
[0008] Generally, the reaction formula of sodium ferrite and carbon dioxide can be recorded as NaFeO2+1 / 2CO2→1 / 2Na2CO3+1 / 2Fe2O3 when the gas does not contain water vapor, and can be recorded as NaFeO2+CO2+1 / 2H2O→NaHCO3+1 / 2Fe2O3 when the gas contains water vapor. Therefore, sodium ferrite theoretically has the ability to adsorb and desorb up to 18 to 30% by weight of carbon dioxide. Prior art literature Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. H05-301023 Patent Document 2: Japanese Patent Application Publication No. 2009-6275 Patent Document 3: Japanese Patent Application Publication No. 2012-139622 Patent Document 4: Japanese Patent Application Publication No. 2006-298707 Patent Document 5: Japanese Patent Application Publication No. 2005-270842 Patent Document 6: Japanese Patent Application Publication No. 2016-3156 Non-patent literature
[0010] Non-patent literature 1: I. Yanase, S. Onozawa, K. Ogasawara, H. Kobayashi, J. CO2 Utilization, Vol. 24, 2018, pp. 200-209 Non-patent document 2: Yanagise Ikuo, Journal of the Society of Inorganic Materials, Japan, Vol. 25, 2018, pp. 437-442 Summary of the invention -Problems to be solved by the invention-
[0011] As described above, carbon dioxide fixation recovery materials made of solid, especially non-hazardous inorganic materials are expected. However, the current carbon dioxide fixation recovery of amine aqueous solution is carried out at about 120°C, while carbon dioxide fixation recovery materials made of inorganic materials such as barium orthotitanate (Patent Document 4) and lithium ferrite (Patent Document 5) adsorb and desorb carbon dioxide in a temperature range of more than 200°C, and the energy cost is worse than that of using amine aqueous solution.
[0012] That is, the use of an aqueous amine solution as a carbon dioxide fixation recovery material described in Patent Documents 1 and 2 is advantageous for large facilities such as thermal power plants, but is not suitable for small and medium-sized facilities that emit carbon dioxide.
[0013] The material described in Patent Document 3 is also a carbon dioxide fixation recovery material containing alkanolamine. However, since dangerous alkanolamine is used, there is a concern about the elution of amine components, and therefore the material is not suitable for small and medium-sized facilities.
[0014] In the description of Patent Document 4, Ba2TiO4 composite oxide is used as a carbon dioxide fixation recovery material. However, since the heating temperature in the carbon dioxide release process is 800 to 1000°C, it is disadvantageous in terms of heating cost.
[0015] Patent Document 5 discloses that a composite oxide containing lithium and iron is used as a carbon dioxide fixation recovery material. However, since the carbon dioxide fixation recovery temperature is 500° C. and the release temperature is 700° C., it is disadvantageous in terms of heating cost.
[0016] Patent Document 6 and Non-Patent Documents 1 and 2 describe the fixation and recovery of carbon dioxide at room temperature, and there are also reports on porous bodies.
[0017] Therefore, the object of the present invention is to provide a composite iron oxide particle powder, and a method for producing the particle powder, wherein the composite iron oxide particle powder can fix carbon dioxide in a temperature range from room temperature to 100°C, recover carbon dioxide by heating below 150°C, and has high formability and processability. -Solutions to solve the problem-
[0018] In order to achieve the above-mentioned purpose, the inventors have conducted in-depth research and found that by using a composite iron oxide particle powder with specified physical properties and composition ratios, carbon dioxide can be fixed in a temperature range from room temperature to 100°C, and the fixed carbon dioxide can be recovered below 150°C, thereby completing the present invention.
[0019] Specifically, the composite iron oxide particle powder of the present invention is characterized in that it contains more than 25 wt% and less than or equal to 60 wt% of at least one sodium carbonate selected from NaHCO3 and Na2CO3, and the molar ratio of Na / Fe is 0.4 to 1.2.
[0020] The sodium carbonate has a basic carbon dioxide absorption and desorption ability, and the reaction formula for absorbing carbon dioxide is represented by Na2CO3+1 / 2CO2+1 / 2H2O→NaHCO3. The reaction formula for desorbing (recovering) carbon dioxide is represented by NaHCO3→1 / 2Na2CO3+1 / 2H2O. However, since sodium carbonate and sodium bicarbonate are relatively stable compounds, even if the sodium carbonate powder itself is placed in the atmosphere or in contact with combustion exhaust gas, the absorption of carbon dioxide will not occur frequently. In addition, even if the sodium bicarbonate is heated below 150°C, the release of carbon dioxide will not occur frequently. Through the coexistence of the above-mentioned sodium carbonate and iron oxide components, it is shown that the trace carbon dioxide present in the atmosphere and the high concentration of carbon dioxide of about 5 to 20% contained in various combustion exhaust gases can be absorbed and fixed, and the fixed carbon dioxide can be recovered below 150°C. Although the details are unknown, due to the iron oxide component contained, the reaction of (Fe2O3+1 / 2Na2CO3)+1 / 2CO2+1 / 2H2O→(Fe2O3+NaHCO3) proceeds quantitatively at low temperatures of 0 to 50°C. In addition, if heated, the reaction of (Fe2O3+NaHCO3)→(Fe2O3+1 / 2Na2CO3)+1 / 2CO2+1 / 2H2O proceeds quantitatively below 150°C.
[0021] Preferably, the axial ratio of the average major axis diameter to the average minor axis diameter of the primary particles of the composite iron oxide particle powder of the present invention is 1-2.
[0022] The granular powder has a small ratio of the average major axis diameter to the average minor axis diameter of primary particles of 1 to 2 and is nearly spherical in shape, so that it can be formed into a granular powder with high dispersibility, in which primary particles are not easily agglomerated, and which has excellent formability and processability.
[0023] Preferably, the powder pH value of the composite iron oxide particle powder of the present invention is 8-14.
[0024] If the powder pH is 8 to 14, the composite iron oxide particle powder of the present invention is alkaline and thus can easily capture weakly acidic carbon dioxide. Furthermore, as described above, free NaOH, Na2CO3 and other alkaline components that cause the gelation of the coating are unlikely to remain, so the coating can be used as a coating with high dispersibility.
[0025] The method for producing composite iron oxide particle powder of the present invention is characterized in that it comprises the steps of mixing iron oxide particle powder and particle powder of sodium raw material and performing solid phase reaction at a temperature of 150° C. to 400° C. in a carbon dioxide atmosphere.
[0026] The method for producing the composite iron oxide particle powder of the present invention mixes solids with solids, and moves elements to react in the absence of a solvent. Since no solvent as a reaction mother liquid is used, waste such as solvents used in liquid phase reactions can be suppressed. In particular, in the case of a low-temperature solid phase reaction, an extremely high concentration reaction can be carried out, so the energy cost can be suppressed to a very low level. First, a solid solution of iron oxide and sodium is formed by mixing and heating the iron oxide particles and a sodium source. Furthermore, by heating in a carbon dioxide atmosphere, the sodium in the solid solution reacts with carbon dioxide, and sodium carbonate and a portion of sodium bicarbonate are uniformly mixed in the iron oxide particles to form composite iron oxide particles. According to the method for producing the composite iron oxide particle powder of the present invention, carbon dioxide can be fixed in a temperature range of room temperature to 100°C, and carbon dioxide can be recovered by heating below 150°C, and composite iron oxide particle powder with high purity and high efficiency and rich formability and processability can be produced. -Effects of the Invention-
[0027] The composite iron oxide particle powder of the present invention can fix carbon dioxide in a temperature range of room temperature to 100° C. using inorganic materials that are not hazardous substances, and recover the fixed carbon dioxide at a temperature below 150° C. In addition, the particle powder has excellent dispersibility after being coated, and is therefore suitable for use as a material with excellent formability and processability. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 These are the results of thermogravimetric analysis of the composite iron oxide particles obtained in Example 1 after fixing carbon dioxide. DETAILED DESCRIPTION
[0029] Hereinafter, the configuration of the present invention will be described in more detail.
[0030] First, the composite iron oxide particles according to one embodiment of the present invention will be described.
[0031] The composite iron oxide particle powder involved in this embodiment contains more than 25 wt% and less than or equal to 60 wt% of at least one sodium carbonate selected from NaHCO3 and Na2CO3. In the case of the above weight % range, the fixation and recovery performance of carbon dioxide can be improved. More preferably, the above weight % range is 30 wt% to 55 wt%.
[0032] The Na / Fe molar ratio of the composite iron oxide particle powder involved in one embodiment of the present invention is 0.4 to 1.2. If the Na / Fe molar ratio is less than 0.4, the generated sodium ferrite particles will have a small content of the powder, and the carbon dioxide fixation and recovery performance will be poor. In addition, if the Na / Fe molar ratio is greater than 1.2, a large amount of alkaline components such as NaHCO3 and Na2CO3 will remain. This alkaline component is also the cause of the gelation of the coating, and it is difficult to say that a highly dispersible coating can be formed, and it is difficult to say that the particle powder has excellent formability and processability. Preferably, the Na / Fe molar ratio is 0.5 to 1.1.
[0033] Preferably, the iron oxide component of the composite iron oxide particle powder involved in this embodiment is any one or more of hematite, hematite, magnetite and goethite. Although the reason is unknown, the iron oxide component preferably contains trivalent iron ions. The content of the iron oxide component is preferably 40% to 75% by weight, and more preferably 45% to 70% by weight.
[0034] Preferably, the composite iron oxide particle powder of the present embodiment has a powder pH of 8 to 14. Since the powder pH is alkaline at 8 or above, it is easy to capture weakly acidic carbon dioxide. On the other hand, if the powder pH is greater than 14, the coating will gel and it will be difficult to achieve high dispersibility. The powder pH is more preferably 12 to 13.5.
[0035] Preferably, the BET specific surface area of the composite iron oxide particle powder involved in this embodiment is 1 m 2 / g~7m 2 / g. If the BET specific surface area is less than 1m 2 / g, it is difficult for the carbon dioxide contained in the gas to come into contact, and the carbon dioxide absorption performance is reduced. In addition, if the BET specific surface area is greater than 7m 2 / g, it is difficult to industrialize the production. The BET specific surface area is more preferably 2m 2 / g~6m 2 / g, and more preferably 2m 2 / g~5.5m 2 / g.
[0036] Preferably, the average primary particle size of the composite iron oxide particle powder involved in this embodiment is 50nm to 1000nm. If the average primary particle size is less than 50nm, it is difficult to industrialize. In addition, if the average primary particle size is greater than 1000nm, the absorption performance of carbon dioxide is reduced. The average primary particle size is more preferably 100nm to 700nm.
[0037] Preferably, the axial ratio (average major axis diameter / average minor axis diameter) of the primary particles of the composite iron oxide particle powder involved in this embodiment is 1.0 to 2.0. When the axial ratio is greater than 2, the primary particles are easily agglomerated with each other, and it is difficult to maintain a high dispersibility after coating. As a result, when the axial ratio is greater than 2, it is difficult to say that the particle powder has excellent formability and processability. In addition, the axial ratio cannot be less than 1. A more preferred axial ratio is in the range of 1.2 to 1.9, and a further preferred range is 1.3 to 1.8.
[0038] When the composite iron oxide particle powder involved in this embodiment is used as a carbon dioxide fixing recovery material, carbon dioxide can be selectively adsorbed and fixed from a gas containing carbon dioxide. The above-mentioned adsorption temperature is room temperature to exhaust port temperature, that is, about 10°C to 100°C. The above-mentioned adsorption temperature is more preferably about 10°C to 50°C. Since no additional external heating is required, the energy cost consumed by adsorption can be reduced (the above is the carbon dioxide fixing process).
[0039] Preferably, the composite iron oxide particles powder involved in this embodiment desorbs the carbon dioxide added in the above carbon dioxide fixation process in a gas atmosphere not containing carbon dioxide at a temperature greater than 50° C. and less than or equal to 150° C. to recover carbon dioxide. Since the desorption temperature is as low as 150° C. or less, the energy cost consumed by desorption can be suppressed (the above is the carbon dioxide recovery process).
[0040] The composite iron oxide particles involved in this embodiment can control the empty tower velocity of the adsorption tower when it is in contact with carbon dioxide as a fixed recovery material for carbon dioxide. That is, the composite iron oxide particles can be granulated or loaded on a carrier to form a spherical molded body with a diameter of about 100 μm to 10 mm. More preferably, it is a spherical molded body with a diameter of 200 μm to 7 mm. The molded body containing the composite iron oxide particles preferably has a diameter of 1 m 2 / g~1000m 2 / g specific surface area, so that even if the diameter of the above-mentioned molded body increases, it will not hinder the contact with carbon dioxide. In addition, the shape of the molded body is not particularly limited, and in addition to a spherical shape, a spindle shape, a rectangular parallelepiped shape, a dice shape, etc. are also preferred. In addition, the composite iron oxide particle powder can be made into a coating and applied to a grid, a non-woven fabric, a honeycomb, etc. to fix and recover carbon dioxide, or the composite iron oxide particle powder can be filled into a column to make a filter to fix and recover carbon dioxide.
[0041] Next, a method for producing composite iron oxide particles according to one embodiment of the present invention will be described.
[0042] The composite iron oxide particles according to the present embodiment can be obtained by mixing iron oxide particles and sodium raw material particles and heating the mixture at a temperature of 150° C. to 400° C. in a carbon dioxide atmosphere to perform a solid phase reaction.
[0043] By mixing and heating the iron oxide particles and the sodium source, a solid solution of iron oxide and sodium is obtained. Then, by heating in a carbon dioxide atmosphere, the sodium in the solid solution reacts with carbon dioxide to form composite iron oxide particles in which sodium carbonate and a portion of sodium bicarbonate are uniformly mixed in the iron oxide particles.
[0044] As the iron oxide particle powder, hematite, magnetite, maghemite, goethite or the like can be used.
[0045] The shape of the iron oxide particles may be selected from a needle shape, a spindle shape, a granular shape, a sphere, a tetrahedron, a hexahedron, an octahedron and the like.
[0046] The particle size of the iron oxide particles can be any size from 10 nm to 1 μm.
[0047] As the granular powder of the sodium raw material, sodium nitrite, sodium sulfate, sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium oxide, etc. can be used. However, in consideration of industrial use, sodium nitrite, sodium sulfate, etc. which may generate toxic nitrous acid gas, sulfurous acid gas, etc. during production should be avoided.
[0048] Usually, solid phase reaction is a synthetic method in which solids are mixed with solids and elements are moved and reacted in the absence of solvent. Since the solvent as the reaction mother solution is not used, wastes such as the solvent used for liquid phase reaction can be suppressed. In addition, one of the characteristics of the present invention is the solid phase reaction at low temperatures, in which case extremely high concentration reactions can be achieved, so energy costs can also be suppressed. In addition, due to the above-mentioned high reaction concentration and the need for washing, a high yield of the product can also be expected.
[0049] In addition, in the solid phase reaction in the presence of carbon dioxide, a trace amount of water is present at the contact interface between the iron oxide and the sodium source, thereby promoting the acid-base reaction at the contact interface. The atmosphere preferably contains at least 1% carbon dioxide, and more preferably contains 2 to 80% carbon dioxide.
[0050] In addition, in a solid phase reaction at 400° C. or lower using water vapor as a heat source, heat is uniformly transferred at the contact interface between iron oxide and the sodium source, which is preferred.
[0051] <Function> In this embodiment, the composite iron oxide granules contain more than 25% by weight and less than or equal to 60% by weight of at least one sodium carbonate selected from NaHCO3 and Na2CO3, and the molar ratio of Na / Fe is 0.4 to 1.2. The composite iron oxide granules have the excellent performance of further adsorbing carbon dioxide in the gas and sealing it in the solid, and releasing carbon dioxide by heating. Compared with pure NaHCO3 and Na2CO3, they can recover the fixed carbon dioxide at a lower temperature. Although the details are unclear, it is believed that this is due to the catalytic effect caused by the presence of the iron oxide component, which separates carbon dioxide from the complex of the iron oxide component and sodium bicarbonate mixed with carbon dioxide with lower energy, or returns the complex of the iron oxide component and sodium carbonate with lower energy. In addition, in the granules described in the present invention, the molar ratio of Na / Fe is 0.4 to 1.2, so it can contain a large amount of sodium components, and the fixed recovery performance of carbon dioxide is good. Furthermore, since the proportion of Na is not too high, free NaOH, Na2CO3 and other alkaline components that cause gelation of the coating are unlikely to remain when the particles are made into coatings, so a highly dispersible coating can be formed. Combining these characteristics, the composite iron oxide particles of the present invention can fix carbon dioxide in a temperature range of room temperature to 100°C and recover the fixed carbon dioxide at a temperature below 150°C. [Example] Representative embodiments of the present invention are shown below.
[0053] The element analysis (except oxygen) in the composite iron oxide particles and raw materials of the present invention was performed using a scanning fluorescent X-ray analyzer ZSX PrimusII manufactured by Rigaku Corporation.
[0054] The weight percent of the crystalline phase of the composite iron oxide particle powder of the present invention is identified and quantified using a fully automatic multifunctional X-ray diffraction device D8 ADVANCE manufactured by Bruker Corporation.
[0055] The BET specific surface area of the composite iron oxide particle powder of the present invention is measured by the BET method using nitrogen using Multisorb-16 manufactured by QUANTA CHROME.
[0056] The average major axis diameter and the average minor axis diameter of the primary particles of the composite iron oxide particles of the present invention are obtained by measuring the major axis diameter and the minor axis diameter of 350 primary particles shown in a microscope photograph using a scanning electron microscope S-4800 manufactured by Hitachi High-Tech Corporation, and expressing the average value thereof.
[0057] The axial ratio of the composite iron oxide particles of the present invention is represented by the ratio of the average major axis diameter to the average minor axis diameter (average major axis diameter / average minor axis diameter).
[0058] The average primary particle size of the composite iron oxide particle powder of the present invention is represented by the average value of the average major axis diameter and the average minor axis diameter.
[0059] The powder pH value of the composite iron oxide particle powder described in the present invention is determined in the following manner: 5 g of a sample is weighed in a 300 ml conical flask, 100 ml of boiling pure water is added, and the mixture is heated and kept boiling for about 5 minutes, then the stopper is covered and the mixture is cooled to room temperature, water corresponding to the weight loss is added, the stopper is covered again, and the mixture is shaken and mixed for 1 minute. After standing for 5 minutes, the pH value of the obtained supernatant is measured according to Japanese Industrial Standard JIS Z8802-7, and the obtained value is used as the powder pH value.
[0060] The carbon dioxide fixation and recovery capacity of the composite iron oxide particle powder described in the present invention is determined in the following manner: 100 mg of the sample is placed on a combustion boat and placed in an acrylic tube with inlet and outlet pipes, and a mixed gas (carbon dioxide + nitrogen) with a humidity adjusted to a range of 20 to 100% and a carbon dioxide concentration adjusted to a range of 1 to 100 vol% is introduced from the inlet at 500 mL / min. The carbon dioxide absorption amount after 2 hours is measured using a differential thermal-thermogravimetric simultaneous measurement device STA7000 manufactured by Hitachi High-Tech Corporation, and the temperature is raised from room temperature to 200°C. The fixed carbon dioxide recovery amount is determined based on its thermal weight loss.
[0061] The dispersibility evaluation of the composite iron oxide particle powder of the present invention is carried out in the following manner: 10 parts by weight of the composite iron oxide particle powder is weighed, and 1 part by weight of alkylamine, 89 parts by weight of propylene glycol monomethyl ether acetate, and 100 parts by weight of 1.5 mm glass beads are added. Then, the above mixture is shaken in a paint conditioner for 2 hours, and the glass beads are filtered out from the slurry. The obtained slurry is measured for dispersed particle size using a concentrated particle size analyzer FPAR1000 manufactured by Otsuka Electronics. When the cumulative 50% value (D50) of the scattering intensity distribution is less than 2 times the average primary particle size, it is judged as a sample with good dispersibility and evaluated as "○", and when it is greater than 2 times, it is evaluated as "×".
[0062] <Method for producing composite iron oxide particles> Example 1 Iron oxide particles 1 (100ED manufactured by TODA KOGYO CORP., hematite, specific surface area 11 m 2 / g) 10 parts by weight, weigh sodium raw material sodium hydroxide granules and add them to the iron oxide particles 1 so that Na / Fe=1.0 (molar ratio). After mixing the raw materials, mix and grind them with a sample mill. The mixed and ground material is placed in a crucible and subjected to solid phase reaction at 400°C in a nitrogen atmosphere containing 10% carbon dioxide for 16 hours. Then, it is cooled to room temperature and ground with a sample mill to obtain a composite iron oxide granule powder. The BET specific surface area of the obtained granule powder is 4.0 m 2 / g. The primary particles were quantified by scanning electron microscopy, with an average major axis diameter of 0.7μm, an average minor axis diameter of 0.4μm, an average primary particle size of 0.55μm, and an axial ratio of 1.8. The pH value of the powder was 13.8.
[0063] The elemental analysis contained in the obtained composite iron oxide particle powder was carried out using fluorescent X-rays, and the result showed that the molar ratio of Na / Fe was 1.0. In addition, the obtained powder was quantified by the powder X-ray diffraction pattern and was found to be 51 weight % of sodium carbonate and 49 weight % of hematite (γ-Fe2O3).
[0064] In order to study the carbon dioxide fixation and recovery performance of the obtained composite iron oxide particle powder, 1.00 weight parts of the sample was placed on a No. 2 combustion boat (12×60×9mm), and a model combustion exhaust gas was passed through at 500mL / min for 3 hours. Generally, the exhaust gas when the fuel is burned in the atmosphere consists of a maximum of 80vol% nitrogen, 20vol% carbon dioxide, and a humidity of 80-100%. Therefore, 400mL / min of nitrogen and 100mL / min of carbon dioxide were mixed at room temperature 25°C and bubbles were blown into water to prepare a model combustion exhaust gas with 20vol% carbon dioxide and a relative humidity RH80%.
[0065] Weigh 10 mg of the ventilated sample, pass dry air through the thermogravimetric device at 300 mL / min, and raise the temperature to 200°C at 10°C / min to measure the desorption temperature and desorption amount of carbon dioxide adsorbed on the sample. The measurement graph with the horizontal axis representing the sample temperature is shown in Figure 1 The TG curve is the weight % of the residual sample at each temperature when the initial value is set to 100 weight %, and the reduction in the sample is considered to be caused by the release of carbon dioxide. The DTG curve is a differential curve of the TG curve, and the temperature at which the DTG curve takes the maximum value is considered to be the desorption temperature of carbon dioxide. The DTA curve is a downwardly convex curve, and it can be seen that the endothermic reaction occurs at around 99°C. It is considered to be a thermal decomposition reaction of NaHCO3 and is quantified. The result shows that the desorption temperature of carbon dioxide is 93°C and the desorption amount of carbon dioxide is 8 weight % relative to the sample solid content, indicating excellent carbon dioxide fixation and recovery performance.
[0066] Furthermore, the sample after ventilation was re-prepared, and the weight was measured, and the result was 1.40 parts by weight, confirming a mass increase of 40% by weight. The X-ray diffraction of the sample was measured, and the results confirmed that NaHCO3 and γ-Fe2O3 were found. It is believed that carbon dioxide was absorbed and a reaction of 1 / 2Na2CO3+CO2+H2O→NaHCO3 occurred. Furthermore, the sample was heated in an electric furnace at 120°C for 1 hour, and the weight was measured, and the result was 1.32 parts by weight. It can be seen that 0.08 parts by weight (8% by weight relative to the solid matter) of carbon dioxide can be adsorbed and desorbed in this cycle. Furthermore, as described above, if carbon dioxide is brought into contact with the sample, the amount increases to 1.40 parts by weight, and if heated, the amount decreases to 1.32 parts by weight, and 0.08 parts by weight of carbon dioxide can be adsorbed and desorbed. This operation was repeated 10 times, and it was confirmed that there was no change in the increase or decrease in mass. This shows that the composite iron oxide particle powder has excellent carbon dioxide fixation and recovery performance, especially excellent repeatability.
[0067] The dispersibility of the obtained composite iron oxide particle powder was evaluated. As a result, the dispersed particle size was within 2 times the average primary particle size, which was evaluated as good.
[0068] Embodiments 2 to 5 The composite iron oxide particle powder of the present invention was obtained in the same manner as in Example 1 except that the types and amounts of the iron oxide fine particles and the sodium source were variously changed.
[0069] The manufacturing conditions in these examples are shown in Table 1, various properties of the obtained composite iron oxide particle powder are shown in Table 2, and the carbon dioxide fixation recovery performance and dispersibility are shown in Table 3. The carbon dioxide recovery performance was evaluated as follows: 10 g of the carbon dioxide absorbent was placed in a dryer (13 L) with a carbon dioxide concentration of 4000 ppm. After 30 minutes, the carbon dioxide absorbent with a carbon dioxide concentration of 2500 ppm or less was rated as ○, and the carbon dioxide absorbent with a carbon dioxide concentration of more than 2500 ppm was rated as ×. The sample with good dispersibility was rated as ○, and the sample with poor dispersibility was rated as ×, which is recorded in Table 3.
[0070] Comparative Example 1 Weigh 10 parts by weight of iron oxide 1, weigh sodium hydroxide granules to make Fe:Na=1:1 (molar ratio), add 100 parts by weight of pure water to dissolve the sodium hydroxide granules, and knead for 2 hours using an automatic mortar. Dry it at 80°C for 2 hours, mix and crush it using a sample mill. Put the mixed crushed product into a crucible and heat treat it at 400°C for 16 hours. Powder X-ray diffraction shows that the product contains 25% by weight of sodium carbonate. The BET specific surface area is 1.0m 2 / g. The axial ratio was 3.8. In addition, the fixation and recovery performance of carbon dioxide was examined in the same manner as in the examples. As a result, desorption of carbon dioxide was not confirmed even though the temperature was raised to 200°C.
[0071] The production conditions of this comparative example are shown in Table 1, various properties of the obtained composite iron oxide particles are shown in Table 2, and the carbon dioxide fixation and recovery performance and dispersibility thereof are shown in Table 3.
[0072] [Table 1]
[0073] [Table 2]
[0074] [Table 3]
[0075] The above results show that the composite iron oxide particles of the present invention can be used as a solid carbon dioxide recovery material having excellent carbon dioxide adsorption and desorption properties. In addition, the particles have excellent dispersibility and are therefore highly moldable and processable. -Industrial Applicability-
[0076] The composite iron oxide particle powder described in the present invention is a material for fixing and recovering greenhouse gases, especially carbon dioxide, as part of a global warming countermeasure. It is suitable as a material for fixing and recovering carbon dioxide by adsorption and desorption using non-hazardous inorganic materials without using hazardous substances such as amine aqueous solutions.
Claims
1. A composite iron oxide particle powder, characterized in that: The composite iron oxide particle powder contains more than 25 wt % and less than or equal to 60 wt % of at least one sodium carbonate selected from NaHCO 3 and Na 2 CO 3 , and the molar ratio of Na / Fe is 0.4 to 1.
2.
2. The composite iron oxide particle powder according to claim 1, characterized in that: The iron oxide component of the composite iron oxide particle powder is at least one of maghemite, hematite, magnetite and goethite.
3. The composite iron oxide particle powder according to claim 1 or 2, characterized in that: The composite iron oxide particles have an axial ratio of an average major axis diameter to an average minor axis diameter of primary particles of 1 to 2.
4. The composite iron oxide particle powder according to claim 1 or 2, characterized in that: The powder pH value of the composite iron oxide particle powder is 8-14.
5. A method for producing composite iron oxide particles, which is the method for producing composite iron oxide particles according to claim 1 or 2, characterized in that: The method for producing the composite iron oxide particle powder comprises the steps of mixing the iron oxide particle powder and the sodium raw material particle powder, and performing a solid phase reaction at a temperature of 150° C. to 400° C. in a carbon dioxide atmosphere.
Citation Information
Patent Citations
Carbon dioxide absorber, method and apparatus for absorbing carbon dioxide, carbon dioxide separator, and process for producing lithium composite oxide
JP2005270842A
Method for separating and recovering carbon dioxide and separating and recovering apparatus of carbon dioxide
JP2006298707A
Efficient recovering method of carbon dioxide in exhaust gas
JP2009006275A
Solid absorber for separating / recovering carbon dioxide and method for recovering carbon dioxide
JP2012139622A
Method for manufacturing α-sodium ferrite
JP2016003156A